Demystifying Success : The New Structural Economics Approach - Lin, Justin Yifu (2012)
It took a Scottish moral philosopher with no training in economics to set the course of modern economics and challenge researchers to answer what is arguably the most fundamental question in public policy, namely: what is the recipe for growth, job creation, and poverty reduction?